THE ERROR ANALYSIS OF THE PRONUNCIATION OF DENTAL FRICATIVE CONSONANTS (/θ/,/ð/) BY THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM FACULTY OF TEACHER TRAINING AND EDUCATION SRIWIJAYA UNIVERSITY - Dedi Kurniawan (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
Abstract: Pronunciation is one of the key factors in communication. An error in pronunciation might cause a miscommunication in meaning. This descriptive analytical descriptive study tries to find pattern in error of the pronunciation of dental fricative consonants (/θ/,/ð/)  by students of English Education Study Program Faculty of Teacher Training and Education Sriwijaya University on the onset, in the middle and coda of a word. A randomly taken sample of 120 students was taken from a population of 240 students of the study program. The sample was asked to pronounce 30 words in which some of the words were distractors and the rest contained the consonants on onset, in medial and coda. The pronunciations were recorded and then analyzed. A native speaker of English was involved in analyzing the errors. The results show that in pronouncing the two consonants the most errors that arise are that they were pronounced as /t/, /d/ which is the closest equivalents of the consonants in Bahasa Indonesia. While other sounds, i.e. /s/, /d/, /θ/, and /ð/, also occurs but in much lower frequency. It is suggested that the result of the study can be used in other similar studies and also used as teaching and learning material in relevant courses. Keywords: errors, pronunciation, dental fricatives, consonant